Answer:
y-incercepts:
sinh(x):0, cosh(x)=1
Limits:
positive infinity: sinh(x): infinity, cosh(x): infinity
negative infinity: sinh(x): - infinity, cosh(x): infinity
Step-by-step explanation:
We are given that
[tex]\sinh(x)=\frac{e^{x}-e^{-x}}{2}[/tex]
[tex]\cosh(x)=\frac{e^{x}+e^{-x}}{2}[/tex]
To find out the y-incerpt of a function, we just need to replace x by 0. Recall that [tex]e^{0}=1[/tex]. Then,
[tex]\sinh(0) = \frac{1-1}{2}=0[/tex]
[tex]\cosh(0) = \frac{1+1}{2}=1 [/tex]
For the end behavior, recall the following:
[tex]\lim_{x\to \infty}e^{x} = \infty, \lim_{x\to \infty}e^{-x} = 0[/tex]
[tex]\lim_{x\to -\infty}e^{x} = 0, \lim_{x\to -\infty}e^{-x} = \infty[/tex]
Using the properties of limits, we have that
[tex]\lim_{x\to \infty} \sinh(x) =\frac{1}{2}(\lim_{x\to \infty}e^{x}-\lim_{x\to \infty}e^{-x})=(\infty -0) = \infty[/tex]
[tex]\lim_{x\to \infty} \cosh(x) =\frac{1}{2}(\lim_{x\to \infty}e^{x}+\lim_{x\to \infty}e^{-x}) =(\infty -0)= \infty[/tex]
[tex]\lim_{x\to -\infty} \sinh(x) =\frac{1}{2}(\lim_{x\to -\infty}e^{x}-\lim_{x\to -\infty}e^{-x}) = (0-\infty)=-\infty[/tex]
[tex]\lim_{x\to -\infty} \cosh(x) =\frac{1}{2}(\lim_{x\to -\infty}e^{x}+\lim_{x\to -\infty}e^{-x}) =(0+\infty)= \infty[/tex]